RECURRENT APTHOUS STOMATITIS – A REVIEW - J, Aishwarya; BRUNDHA MP (Innovare Journal Health Sciences, 2018)
ABSTRACT: Apthous stomatitis is a most common condition which affects the oral cavity and it is painful. Apthous ulcer is characterized by repeated occurrence of benign and non-contagious mouth ulcers. It can be caused due to triggering of T-cell mediated immune response, by various factors. This condition is very common, affecting about 15-20% of the population. The lesions generally occur on the cheeks, lips, gums, floor and roof of the mouth. There are three different types of apthous stomatitis they are apthous ulcer major, apthous ulcer minor and herptiform ulcers. It can be also termed as recurrent apthous ulcer, recurring oral aphthae, and recurrent apthous ulceration. Informal term is canker sores.